Republic of Mozambique : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Modification of Performance Criteria-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report, 2006)
This paper discusses Mozambique's Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Modification of Performance Criteria. Performance under the program has been broadly satisfactory so far in 2005. All quantitative and structural performance criteria have been met through end-September. The two structural benchmarks for end-June were not met; however, one of the corresponding measures was implemented in August and the other is expected to be implemented by end-April 2006. The fiscal program is also on track.